2021
DOI: 10.1093/ibd/izab301
|View full text |Cite
|
Sign up to set email alerts
|

Anti-SARS-CoV-2 Vaccination and Antibody Response in Patients With Inflammatory Bowel Disease on Immune-modifying Therapy: Prospective Single-Tertiary Study

Abstract: Background Patients with inflammatory bowel disease (IBD) on immune-modifying treatment could be at an increased risk for severe coronavirus disease 2019 (COVID-19); thus, data on the efficacy and safety of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) vaccines are essential. We conducted a prospective study of IBD patients vaccinated with BNT162b2, CX-024414, and ChAdOx1 nCoV-19 vaccines. The aim was to evaluate the rate and magnitude of seroconversion, assess the effect of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 13 publications
8
28
0
Order By: Relevance
“…Six months after the second vaccination, IBD patients on anti-TNF therapy (adalimumab, infliximab) also showed significantly lower sVNT levels. These results support the study by Kennedy et [22,39]. Taken together, our study revealed a reduced humoral response in both S-IgG levels and sVNT inhibition levels in IBD patients, especially in patients treated with anti-TNF agents.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Six months after the second vaccination, IBD patients on anti-TNF therapy (adalimumab, infliximab) also showed significantly lower sVNT levels. These results support the study by Kennedy et [22,39]. Taken together, our study revealed a reduced humoral response in both S-IgG levels and sVNT inhibition levels in IBD patients, especially in patients treated with anti-TNF agents.…”
Section: Discussionsupporting
confidence: 93%
“…These results support the study by Kennedy et al which demonstrated lower antibody levels in IBD patients receiving infliximab therapy 3–10 weeks after the first vaccination [ 21 ]. Wong et al and Cerna et al also demonstrated lower antibody levels in IBD patients on immunosuppressive therapy with anti-TNF therapy and vedolizumab [ 22 , 39 ]. Taken together, our study revealed a reduced humoral response in both S-IgG levels and sVNT inhibition levels in IBD patients, especially in patients treated with anti-TNF agents.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, 21 studies were included in their entirety as shown in Table 1. These included 11 prospective studies, seven retrospective studies and three survey‐based studies 16–21,27–41 . The PRISMA Flow chart is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…These included 11 prospective studies, seven retrospective studies and three survey‐based studies. 16 , 17 , 18 , 19 , 20 , 21 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 The PRISMA Flow chart is shown in Figure 1 . The study details are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The details of the included studies are illustrated in Table 1 [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] . The details of the excluded studies with the reason for exclusion is shown in Supplementary Table 2 [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] .
Figure 1 PRISMA flow chart depicting the study screening and selection of the systematic review
…”
Section: Resultsmentioning
confidence: 99%